The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1159/000136903
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Experimentally Induced Choroidal Neovascularizations in Pigmented Rabbits by Subretinal Injection of Lipid Hydroperoxide and Consecutive Preliminary Photodynamic Treatment with Tookad

Abstract: Purpose: Up to date several approaches have been undertaken to achieve an ‘easy-to-handle’ animal model of choroidal neovascularizations (CNVs) in rabbits; however, so far in none of the studies could healthy retinal tissue be maintained, which is mandatory to further investigate the effects of photodynamic therapy (PDT) or anti-vascular-endothelial-growth-factor treatments. It was our aim to reevaluate and verify the method of inducing experimental CNVs in rabbits using subretinally injected linoleic acid hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Previously we reported that dietary intake of omega-3 long-chain polyunsaturated fatty acid (LCPUFA) reduces pathological retinal angiogenesis in oxygen-induced retinopathy [ 17 ]. Several previous studies also report protective effects of omega-3 dietary lipids and their metabolites on laser-induced CNV in rabbits and rats [ 18 , 19 ]. To evaluate the use of the image-guided laser-induced CNV model in the evaluation of potential treatments, we analyzed the effect of dietary LCPUFAs feed on CNV development.…”
Section: Resultsmentioning
confidence: 89%
“…Previously we reported that dietary intake of omega-3 long-chain polyunsaturated fatty acid (LCPUFA) reduces pathological retinal angiogenesis in oxygen-induced retinopathy [ 17 ]. Several previous studies also report protective effects of omega-3 dietary lipids and their metabolites on laser-induced CNV in rabbits and rats [ 18 , 19 ]. To evaluate the use of the image-guided laser-induced CNV model in the evaluation of potential treatments, we analyzed the effect of dietary LCPUFAs feed on CNV development.…”
Section: Resultsmentioning
confidence: 89%